Microencapsulation of Lactobacillus plantarum by spray drying with mixtures of Aloe vera mucilage and agave fructans as wall materials. (22nd May 2020) - Ceja‐Medina, Luis Isaac; Ortiz‐Basurto, Rosa Isela; Medina‐Torres, Luis; Calderas, Fausto; Bernad‐Bernad, Maria Josefa; González‐Laredo, Ruben Francisco; Ragazzo‐Sánchez, Juan Arturo; Calderón‐Santoyo, Montserrat; González‐ávila, Marisela; Andrade‐González, Isaac; Manero, Octavio
Abstract: In this work, a spray‐drying process is used to encapsulate a probiotic strain of Lactobacillus plantarum with mixtures of Aloe vera mucilage (AVM) ( Aloe barbadensis Miller) and agave fructans of high degree of polymerization (AFHDP). Physicochemical properties of the powders reveal moisture contents lower than 10% and water activity between 0.195 and 0.3, suggesting stability during storage. A non‐Newtonian shear‐thinning behavior arises in the reconstituted powders under steady shear flow and viscosity is shown to depend on the concentration, pH, and temperature. A predominant viscous behavior is exhibited in the viscoelastic properties under small amplitude oscillatory flow with equal values of the elastic and viscous moduli at high frequencies ( G ´ = G ´´), suggesting a random coil conformation. Scanning electron microscope observations reveal a spherical microcapsule morphology possessing homogeneous surfaces with modal particle‐size distribution (D [4, 3] =21.3 μm). The addition of arabic gum to the AVM‐AFHDP mixtures induces a shift in the glass transition temperature ( T g ) to 150°C. Preserved stability of the AVM‐AFHDP functional groups with the probiotic after spray drying reveals the effective encapsulation of the microorganism, as corroborated by transmission electron microscopy and Fourier‐transform infrared. Enhanced microorganism survival rate of 70% in the mixture is recorded, representing an alternative for probiotic encapsulation. PRACTICAL APPLICATIONS: Nowadays, the use of mixtures of prebiotic biopolymers as encapsulating wall materials is highly appreciated by the food and pharmaceutical industry. This research demonstrated that mixtures of Aloe vera mucilage and agave fructans are suitable for the microencapsulation of L. plantarum through studies on their rheological, morphological, and calorimetric properties. High survival rates and stable powders are obtained in samples subjected to spray drying. Results of this investigation may help to develop new delivery drug systems, which are able to protect bioactive compounds or probiotic cells through the gastrointestinal tract. Increasing health benefits, including probiotic and symbiotic effects, are expected with the intake of dietary fibers. Abstract :